2012
DOI: 10.3109/15376516.2012.731437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zn deficiency, antioxidants, and low-dose radiation on diabetic oxidative damage and cell death in the testis

Abstract: Infertility is one of the common complications in diabetic men and mainly due to the loss of germ cells by apoptotic cell death. Although several mechanisms have been proposed to explain the induction of testicular cell death by diabetes, diabetic induction of testicular oxidative stress and damage may be the predominant mechanism responsible for the testicular cell death in diabetes. To explore whether factors that either increase or decrease the testicular oxidative stress and damage will enhance or prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…Studies with animal models from our own laboratory have clearly indicated that male germ cell death in T1DM mice or rats was mediated predominantly by the mitochondrial cell death pathway (45,50) and also the ER stress cell death pathway (47). In an animal study where mice were exposed to cadmium, testicular cell death was increased significantly via the ER stress pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with animal models from our own laboratory have clearly indicated that male germ cell death in T1DM mice or rats was mediated predominantly by the mitochondrial cell death pathway (45,50) and also the ER stress cell death pathway (47). In an animal study where mice were exposed to cadmium, testicular cell death was increased significantly via the ER stress pathway.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM features two physiological defects: peripheral tissue's resistance to the action of insulin and a deficiency in insulin secretion at late stage (Andrikopoulos et al, 2008; Taylor, 1999). Accordingly an insulin-defective stage of T2DM (IDS-T2DM) rat model was created by high-fat diet (HFD) feeding containing 60 kcal% fat for 2 months to induce insulin resistance, followed by a small dose (25 mg/kg of body weight) of STZ (Sigma Aldrich, St. Louis, MO, USA) to cause mild deficiency of insulin with hyperglycemia, as described in our previous (Zhao et al, 2013) and other studies (Kusakabe et al, 2009; Luo et al, 1998; Mu et al, 2006). Control rats were fed with the control diet (CD), containing 10 kcal% fat.…”
Section: Methodsmentioning
confidence: 99%
“…75 mg/kg STZ induced diabetes (27). Zhao et al determined an increase in the apoptotic cell count and a decrease in SOD, TSH and LH in the testis tissue of rats 2 months after the onset of diabetes (28). In another study, it was reported that LH and FSH decreased, and this decrease was more than 50 % in serum testosterone in 12-week diabetic rats (29).…”
Section: Discussionmentioning
confidence: 96%